2020
DOI: 10.3389/fphys.2020.00893
|View full text |Cite
|
Sign up to set email alerts
|

Eight-Week Low-Intensity Squat Training at Slow Speed Simultaneously Improves Knee and Hip Flexion and Extension Strength

Abstract: Considering that the squat exercise requires flexion and extension of the knee and hip joints, a resistance training program based on squat exercises should efficiently increase the flexion and extension strength of both the knee and hip. To our knowledge, however, no study has simultaneously investigated the effects of squat training on both flexion and extension strength in both the knee and hip. Low-intensity squat exercises at slow speeds can be expected to effectively and safely improve knee and hip flexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Similar findings were noted by Earp et al [ 12 ] and Zabaleta-Korta et al [ 13 ], where parallel squat RT resulted only in an increase in CSA of the vasti muscles, suggesting that for targeting the RF muscle, single-joint exercises may be a better option [ 14 ]. However, some of the recent studies have reported opposite results [ 15 , 16 , 17 ]. Wilson et al [ 16 ] investigated the effects of different RT exercise prescriptions (squat vs. deadlift vs. hip thrust) on VL and RF muscle thickness and found that all training modalities increased the size of tested muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were noted by Earp et al [ 12 ] and Zabaleta-Korta et al [ 13 ], where parallel squat RT resulted only in an increase in CSA of the vasti muscles, suggesting that for targeting the RF muscle, single-joint exercises may be a better option [ 14 ]. However, some of the recent studies have reported opposite results [ 15 , 16 , 17 ]. Wilson et al [ 16 ] investigated the effects of different RT exercise prescriptions (squat vs. deadlift vs. hip thrust) on VL and RF muscle thickness and found that all training modalities increased the size of tested muscles.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that despite the significant group difference in the changes in RFp shear modulus, peak change in the modulus was not associated with the recovery rate of MVIC torque ( Figure 3 ). The RF muscle volume is the smallest among the constituents of the quadriceps femoris, with its proportional contribution to the total quadriceps femoris being not more than approximately 15% ( Ema et al, 2018 ; Akagi et al, 2020 ). Therefore, a possible impact of individual variability of RF damage on the variability of MVIC torque may have been masked, resulting in insignificant correlations between the recovery rate and change in RFp shear modulus.…”
Section: Discussionmentioning
confidence: 99%
“…This exercise is ideal for a home workout program because it does not require any extra equipment. Squat exercises require the patient's knee and hip joints to flex and extend to develop the body part's flexion and extension strength [22]. Hip, knee, and ankle movements must be synchronized correctly to ensure efficient muscle function and avoid damage throughout the activity [23].…”
Section: Rehabilitation Exercisementioning
confidence: 99%